Should male children be vaccinated against human papillomavirus? (2017)
Human papillomavirus (HPV) is the main risk factor for the development of cervical cancer in women and other types of malignancies in men, including penile, oropharyngeal and perianal cancer. These neoplasms take longer to be detected because the infection is asymptomatic and silent in men